Relationship between pectoralis major stiffness and shoulder extension range of motion - Konrad, Andreas; Reiner, Marina M.; Warneke, Konstantin; Keiner, Michael; Nakamura, Masatoshi; Tilp, Markus (Frontiers in Physiology, 2024)
This study aimed to correlate the passive muscle stiffness of the pectoralis major muscle pars clavicularis (PMaPMc) and shoulder extension range of motion (ROM) in both male and female participants. Thirty-nine (23 males/16 females) physically active and healthy participants volunteered in this study. After a standardized warm-up, the PMaPMc muscle stiffness was tested via shear wave elastography at a slightly stretched position (long muscle length) as well as in a non-stretched position (short muscle length). Additionally, a custom-made device and 3D motion capture assessed the active shoulder extension ROM. We found a significant moderate and negative relationship in shoulder extension ROM to PMaPMc stiffness at long muscle length (rs = -0.33; p=0.04) but not at short muscle length (r = -0.23; p=0.17). Additionally, there was no significant difference between males and females in the correlation analyses at both elbow angles. The moderate correlation of PMaPMc stiffness at a slightly stretched position to shoulder extension ROM suggests that additionally, other structures such as nerves/fascia stiffness or even stretch tolerance might be factors that can be related to shoulder extension ROM.